Printed wiring board and semiconductor device
By extending the resin sheet in the via hole of the printed circuit board, the adhesion between the copper foil and the layering material is enhanced, the problems of insufficient adhesion and damage to the copper foil in the prior art are solved, and the reliability of the circuit board is improved.
Patent Information
- Application Number
- JP2021212352
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-03-31
AI Technical Summary
In the prior art, the adhesion between the layering material of the printed circuit board and the copper foil is insufficient, and the copper foil is easily damaged during the via hole formation process, resulting in low reliability of the circuit board.
In the via hole of the printed circuit board, the resin sheet extends from the via hole side wall to the first circuit layer, and by controlling the length and thickness of the resin sheet, the adhesion of the copper foil to the layering material is enhanced, and the over-etching of the resin layer during the via hole formation process is reduced.
The adhesion between the copper foil of the printed circuit board and the construction material is improved, the reliability of via holes is enhanced, and the risk of copper foil damage is reduced, thereby improving the reliability of the overall circuit board.
Smart Images

Figure 0007647540000013 
Figure 0007647540000001 
Figure 0007647540000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a printed wiring board and a semiconductor device. [Background technology]
[0002] In recent years, with the demand for electronic devices to have higher functionality and to be lighter, thinner, shorter, and smaller, the integration and mounting of electronic components has become more dense. In response to this demand, printed wiring boards with higher wiring density and multiple laminated wiring layers are being used. Printed wiring boards are composed of a core layer and multiple build-up layers laminated on the core layer. For example, there is a printed wiring board described in Patent Document 1.
[0003] The method for manufacturing the core layer of the printed wiring board described in Patent Document 1 is as follows. First, a substrate-containing insulating layer is prepared in which the substrate is unevenly distributed downward, and a metal foil is formed on one side of the substrate-containing insulating layer. A carbon gas laser is irradiated onto the surface of the substrate-containing insulating layer on which the metal foil is not formed. Patent Document 1 describes that the substrate protruding from the side wall of the lower part of the via is completely removed by using the reflected light of the laser from the metal foil. This makes it possible to smooth the entire surface of the inner wall of the via, thereby greatly improving the plating throwing power.
[0004] Furthermore, Patent Document 2 discloses that the plating properties of a via hole can be improved by forming the via into an hourglass shape. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2001-277426 A [Patent Document 2] JP 2015-82661 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, in the conventional techniques disclosed in Patent Documents 1 and 2, the adhesion between the build-up layer having via holes and the metal foil such as copper foil was sometimes insufficient. Also, due to damage to the copper foil during the formation of the via holes, there was room for improvement in the reliability of the circuit board having such a build-up layer. [Means for solving the problem]
[0007] In recent years, electronic devices have become smaller and more powerful, and in printed wiring boards, build-up layers have become multi-layered, and wiring has become finer and denser. For this reason, insulating materials with low dielectric tangents are required to reduce transmission loss. The present inventors have focused on the development of a new printed wiring board using a build-up material with a low dielectric tangent and a low dielectric constant, and have conducted intensive research into the above-mentioned problems. As a result, they have found that in a printed wiring board having a laminate in which a substrate, a first circuit layer, an insulating layer made of a build-up material, and a second circuit layer are laminated in order, it is effective to have a resin piece extending from the side wall of the via hole to the surface of the first circuit layer in a via hole penetrating the insulating layer. In addition, although the details of the mechanism by which the resin piece can solve the problem are not clear, it is presumed that the resin piece contacts the copper foil exposed around the bottom of the via hole, thereby increasing the adhesion between the build-up material and the copper foil, suppressing excessive etching of the thermosetting resin layer during the formation of the via hole, and effectively reducing damage to the copper foil caused by etching. As a result, it is believed that the reliability of the printed wiring board using the build-up material is improved.
[0008] According to the present invention, a substrate having a first circuit layer on one or both sides; an insulating layer disposed on a surface of the first circuit layer of the substrate; a second circuit layer disposed on a surface of the insulating layer; A printed wiring board comprising: the insulating layer has a via hole penetrating the insulating layer and a conductor embedded in the via hole, and the insulating layer has a dielectric constant Dk (23°C, 10 GHz) of 3.0 to 3.6 and a dielectric loss tangent Df (23°C, 10 GHz) of 0.0001 to 0.006 after curing at 200°C for 90 minutes; A printed wiring board is provided having a resin strip extending from a sidewall of the via hole onto a surface of the first circuit layer.
[0009] According to the present invention, there is also provided a semiconductor device in which a semiconductor element is mounted on the circuit layer of the above-mentioned printed wiring board. Effect of the Invention
[0010] According to the present invention, a printed wiring board having improved adhesion to a circuit layer and excellent reliability is provided. [Brief description of the drawings]
[0011] The above objects, as well as other objects, features and advantages, will become more apparent from the preferred embodiments described below and the accompanying drawings.
[0012] [Figure 1] 1A to 1C are cross-sectional process diagrams illustrating a manufacturing procedure for a printed wiring board according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. In all drawings, similar components are given similar symbols and descriptions thereof are omitted where appropriate. In order to avoid complexity, when there are multiple identical components in the same drawing, only one of them may be labeled with a reference symbol, and not all of them. All drawings are for illustrative purposes only. The shapes and dimensional ratios of each component in the drawings do not necessarily correspond to the actual objects.
[0014] In this specification, the term "approximately" means that a range taking into consideration manufacturing tolerances, assembly variations, and the like, is included, unless otherwise specified explicitly. In this specification, the expression "a to b" in the explanation of a numerical range means from a to b, unless otherwise specified. For example, "1 to 5% by mass" means "1% by mass to 5% by mass."
[0015] <<Printed wiring board>> As shown in FIG. 1(d), the printed wiring board 100 of the present embodiment includes a substrate 102 (core layer) having a first circuit layer 104 on one side thereof, an insulating layer 106 provided on the surface of the first circuit layer 104 of the substrate 102, and a second circuit layer 114 provided on the surface of the insulating layer 106. The insulating layer 106 has a via hole 116 penetrating the insulating layer 106 and a conductor 124 embedded in the via hole 116. The insulating layer 106 has a dielectric constant Dk (23° C., 10 GHz) of 3.0 to 3.6 and a dielectric loss tangent Df (23° C., 10 GHz) of 0.0001 to 0.006 when cured at 200° C. for 90 minutes. The insulating layer 106 has a resin piece 130 extending from the side wall of the via hole 116 onto the surface of the first circuit layer 104.
[0016] More specifically, when printed wiring board 100 has multiple via holes, it is sufficient that at least one of the via holes has resin piece 130; however, in order to further improve reliability and adhesion, preferably 10 to 80% of the total number of via holes, and more preferably 20 to 50% of the total number of via holes, have resin piece 130.
[0017] The printed wiring board 100 has a conductor 124 that fills the via hole 116, and a first circuit layer (internal circuit) 104 that is electrically connected to the conductor 124. The first circuit layer 104 abuts against the second surface 20 of the insulating layer 106, and covers and closes the opening of the via hole 116 on the second surface 20 side from the second surface 20 side. The first circuit layer 104 is not configured integrally with the conductor 124, and is a separate body from the conductor 124. The substrate 102 (core layer) may have circuit layers on both sides (not shown).
[0018] The insulating layer 106 is formed from the build-up material of this embodiment. First, the build-up material of this embodiment will be described in detail below.
[0019] <Build-up material> The build-up material of this embodiment includes a thermosetting resin layer, and the thermosetting resin layer, when cured at 200° C. for 90 minutes, has a dielectric constant Dk (23° C., 10 GHz) of 3.0 to 3.6 and a dielectric loss tangent Df (23° C., 10 GHz) of 0.0001 to 0.006.
[0020] When the via hole 116 is observed from above the opening, a resin piece is observed, and the resin piece is in contact with the copper foil exposed around the bottom of the via hole. The region where the resin piece is observed may be in contact with at least a part of the copper foil exposed at the bottom of the via hole, and may be in contact with the copper foil by protruding from the wall surface of the via hole above the copper foil surface.
[0021] In this embodiment, the term "resin pieces" refers to aggregated residue of the build-up material burned by the carbon dioxide laser, and to parts of the build-up material protruding from the side walls of the via holes.
[0022] In this embodiment, the maximum length l of the resin piece from the sidewall of the via hole is preferably 1 to 8 μm, and more preferably 2 to 5 μm. By setting the maximum length l to the above-mentioned lower limit or more, the adhesion between the insulating layer 106 and the first circuit layer 104 is improved and the insulation reliability can be increased, while by setting the maximum length l to the above-mentioned upper limit or less, good conduction between the vias is maintained and the connection reliability can be increased. Furthermore, when the thickness of the resin piece at the maximum length l (μm) is d (μm), d / l is preferably 0.065 to 2.5, and more preferably 0.5 to 2.0. This increases the adhesion area with the copper foil, improving adhesion while maintaining good electrical conductivity. The thickness d (μm) of the resin piece can be, for example, the average value of the thicknesses of the resin pieces obtained by observing the cross section of the via hole using a scanning electron microscope (SEM) and observing multiple via holes. Furthermore, the maximum length l (μm) of the resin piece refers to the longest resin piece when multiple via holes are present.
[0023] In this embodiment, the resin pieces as described above are obtained by controlling the raw materials and combinations of the thermosetting resin layer used in the build-up material, or the manufacturing method of the thermosetting resin layer, while taking into consideration the chemical resistance and heat resistance of the thermosetting resin composition layer.
[0024] [Thermosetting resin layer] In this embodiment, the build-up material includes a thermosetting resin layer, and the thermosetting resin layer, when cured at 200° C. for 90 minutes, has a dielectric constant Dk (23° C., 10 GHz) of 3.0 to 3.6 and a dielectric loss tangent Df (23° C., 10 GHz) of 0.0001 to 0.006.
[0025] The melt viscosity of the thermosetting resin layer of this embodiment at 135° C. is preferably 100 to 8,000 Pa·s, and more preferably 200 to 5,000 Pa·s, which makes it easier to obtain desired resin pieces.
[0026] The thermosetting resin layer of the present embodiment is a layer made of a thermosetting resin composition, a prepreg formed by impregnating a fiber base material with the thermosetting resin composition, or a cured product of the prepreg.
[0027] First, the thermosetting resin composition (hereinafter, also referred to as "resin composition") used in the thermosetting resin layer of the present embodiment will be described.
[0028] The thermosetting resin composition of the present embodiment preferably contains one or more selected from (A) a modified polyphenylene ether copolymer, (B) a maleimide compound, (C) an indene resin, and a polyimide resin. Among them, from the viewpoint of stably obtaining insulation reliability, it is preferable to contain all of (A) a modified polyphenylene ether copolymer, (B) a maleimide compound, and (C) an indene resin. Hereinafter, each component contained in the thermosetting resin composition of the present embodiment will be described in detail.
[0029] (A) Modified polyphenylene ether copolymer The modified polyphenylene ether copolymer (A) of the present embodiment is a modified polyphenylene ether copolymer, and for example, those described in paragraphs 0018 to 0061 of WO 2014 / 203511 can be used. More specifically, they are as follows.
[0030] The modified polyphenylene ether copolymer (A) according to this embodiment is not particularly limited, but is preferably a modified polyphenylene ether whose terminals are modified with a substituent having a carbon-carbon unsaturated bond. The substituent having a carbon-carbon unsaturated bond is not particularly limited, but examples thereof include the substituents represented by the following formula (1).
[0031] [ka]
[0032] In the above formula (1), n represents an integer of 0 to 10, Z represents an arylene group, and R1 to R3 each independently represent a hydrogen atom or an alkyl group.
[0033] In the above formula (1), when n = 0, Z is directly bonded to the end of the polyphenylene ether. Examples of the arylene group of Z include monocyclic aromatic groups such as a phenylene group and polycyclic aromatic groups such as a naphthalene ring, and also include derivatives in which a hydrogen atom bonded to the aromatic ring is substituted with a functional group such as an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group.
[0034] The functional group represented by the above formula (1) may be, for example, a functional group containing a vinylbenzyl group. More specifically, at least one substituent selected from the following formula (2) or formula (3) may be included.
[0035] [ka]
[0036] [ka]
[0037] Furthermore, examples of other substituents having a carbon-carbon unsaturated bond directly bonded to the terminal of the polyphenylene ether include a (meth)acrylate group represented by the following formula (4).
[0038] [ka] In the above formula (4), R4 represents a hydrogen atom or an alkyl group.
[0039] The modified polyphenylene ether of the present embodiment preferably has a hydroxy group, a methacrylic group or a styrene group at both ends, from the viewpoint of achieving both low dielectric properties and good laser processability.
[0040] Moreover, the polyphenylene ether in the modified polyphenylene ether of the present embodiment has a polyphenylene ether chain in the molecule, and preferably has, for example, a repeating unit represented by the following formula (5) in the molecule.
[0041] [ka]
[0042] In the above formula (5), m represents 1 to 50. R5, R6, R7, and R8 are each independent and may be the same or different. R5, R6, R7, and R8 represent a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group. Among these, a hydrogen atom and an alkyl group are preferred.
[0043] The alkyl group is not particularly limited, but is preferably, for example, an alkyl group having 1 to 18 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms. More specific examples include a methyl group, an ethyl group, a propyl group, a hexyl group, and a decyl group. The alkenyl group is not particularly limited, but for example, an alkenyl group having 2 to 18 carbon atoms is preferable, and an alkenyl group having 2 to 10 carbon atoms is more preferable. More specific examples include a vinyl group, an allyl group, and a 3-butenyl group. The alkynyl group is not particularly limited, but for example, an alkynyl group having 2 to 18 carbon atoms is preferable, and an alkynyl group having 2 to 10 carbon atoms is more preferable. More specific examples include an ethynyl group, a prop-2-yn-1-yl group (propargyl group), and the like.
[0044] The alkylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkyl group, but for example, an alkylcarbonyl group having 2 to 18 carbon atoms is preferable, and an alkylcarbonyl group having 2 to 10 carbon atoms is more preferable. More specific examples include an acetyl group, a propionyl group, a butyryl group, an isobutyryl group, a pivaloyl group, a hexanoyl group, an octanoyl group, and a cyclohexylcarbonyl group. The alkenylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkenyl group, but for example, an alkenylcarbonyl group having 3 to 18 carbon atoms is preferable, and an alkenylcarbonyl group having 3 to 10 carbon atoms is more preferable. More specific examples include an acryloyl group, a methacryloyl group, and a crotonoyl group. The alkynylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkynyl group, but for example, an alkynylcarbonyl group having 3 to 18 carbon atoms is preferable, and an alkynylcarbonyl group having 3 to 10 carbon atoms is more preferable. More specific examples include a propioloyl group.
[0045] The method for synthesizing the modified polyphenylene ether according to the present embodiment is not particularly limited as long as it can synthesize a modified polyphenylene ether whose terminal is modified by a substituent having a carbon-carbon unsaturated bond. For example, a method of reacting a polyphenylene ether in which the hydrogen atom of the terminal phenolic hydroxyl group is replaced by an alkali metal atom such as sodium or potassium with a compound represented by the following formula (6) can be mentioned.
[0046] [ka]
[0047] In the above formula (6), like the above formula (1), n represents an integer of 0 to 10, Z represents an arylene group, and R1 to R3 each independently represent a hydrogen atom or an alkyl group. X represents a halogen atom, and specific examples thereof include a chlorine atom, a bromine atom, an iodine atom, and a fluorine atom. Among these, a chlorine atom is preferred.
[0048] The compound represented by the above formula (6) is not particularly limited, but is preferably, for example, p-chloromethylstyrene or m-chloromethylstyrene.
[0049] In addition, the compounds represented by the above formula (6) may be used alone or in combination of two or more of the above-exemplified compounds.
[0050] The raw material polyphenylene ether is not particularly limited as long as it can finally synthesize a desired modified polyphenylene ether.Specific examples of the polyphenylene ether include polyarylene ether copolymers consisting of 2,6-dimethylphenol and at least one of a bifunctional phenol and a trifunctional phenol, and poly(2,6-dimethyl-1,4-phenylene oxide) and other polyphenylene ethers as the main component.More specifically, examples of such polyphenylene ethers include polyphenylene ethers having the structure shown in the following formula (7).
[0051] [ka]
[0052] In the above formula (7), for example, the total value of s and t is preferably 1 to 30. Also, s is preferably 0 to 20, and t is preferably 0 to 20. That is, it is preferable that s represents 0 to 20, t represents 0 to 20, and the total value of s and t represents 1 to 30.
[0053] Commercially available modified polyphenylene ethers in which the terminal hydroxyl groups of the polyphenylene ether of the above formula (7) have been modified with methacryl groups include "SA9000" manufactured by SABIC Innovative Plastics.
[0054] The weight average molecular weight of component (A) is preferably from 500 to 5,000, more preferably from 800 to 4,000, and even more preferably from 1,000 to 3,000. The weight average molecular weight may be measured by a general molecular weight measurement method, and specific examples include values measured using gel permeation chromatography (GPC).
[0055] By making the weight average molecular weight of component (A) equal to or greater than the lower limit, the excellent dielectric properties of polyphenylene ether are exhibited, and the cured product is further provided with excellent adhesion and heat resistance. Since component (A) of this embodiment is modified and has terminal reactive groups, particularly terminal unsaturated double bonds, it is believed that the cured product has an improved glass transition temperature while maintaining low dielectric properties, good laser processability, and sufficiently high heat resistance and adhesion. On the other hand, by adjusting the weight average molecular weight of component (A) to be equal to or less than the above upper limit, the moldability, solvent solubility and storage stability become good.
[0056] The content of component (A) is preferably 1 part by weight or more and 30 parts by weight or less relative to 100 parts by weight of resin solids. By making it 1 part by weight or more relative to 100 parts by weight of resin solids, a low dielectric tangent can be obtained by component (A), and by making it 30 parts by weight or less, resin residue can be suppressed and good laser processability can be obtained. The content of component (A) is more preferably 3 parts by weight or more and even more preferably 5 parts by weight or more relative to 100 parts by weight of resin solids, while more preferably 25 parts by weight or less and even more preferably 20 parts by weight or less relative to 100 parts by weight of resin solids. The resin solid content refers to the resin components in the varnish excluding the filler and the solvent.
[0057] (B) Maleimide Compound The maleimide group of the maleimide compound has a planar structure of a five-membered ring, and the double bond of the maleimide group is highly polar and easily interacts with molecules, so that it exhibits strong intermolecular interactions with the maleimide group, benzene ring, other compounds having a planar structure, and the like, and can suppress molecular motion. Therefore, by including the maleimide compound in the resin composition of the present embodiment, the linear expansion coefficient of the obtained insulating layer can be reduced, the glass transition temperature can be improved, and further, the heat resistance can be improved.
[0058] The maleimide compound is preferably a maleimide compound having at least two maleimide groups in the molecule. Examples of maleimide compounds having at least two maleimide groups in the molecule include compounds having two maleimide groups in the molecule, such as 4,4'-diphenylmethane bismaleimide, m-phenylene bismaleimide, p-phenylene bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, bis-(3-ethyl-5-methyl-4-maleimidophenyl)methane, 4-methyl-1,3-phenylene bismaleimide, N,N'-ethylene dimaleimide, N,N'-hexamethylene dimaleimide, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)sulfone, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethane bismaleimide, and bisphenol A diphenyl ether bismaleimide; and compounds having three or more maleimide groups in the molecule, such as polyphenylmethane maleimide. One of these may be used alone, or two or more may be used in combination. Among these maleimide compounds, 4,4'-diphenylmethane bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, bis-(3-ethyl-5-methyl-4-maleimidophenyl)methane, polyphenylmethane maleimide, and bisphenol A diphenyl ether bismaleimide are preferred because of their low water absorption.
[0059] The content of component (B) is preferably 5 parts by weight to 40 parts by weight, more preferably 8 parts by weight to 35 parts by weight, and even more preferably 10 parts by weight to 30 parts by weight, based on 100 parts by weight of the resin solid content. By making the content of component (B) equal to or greater than the lower limit, it is possible to obtain good dielectric tangent and laser processability while lowering the linear expansion coefficient, increasing the glass transition temperature, and improving heat resistance. On the other hand, by making the content of component (B) equal to or less than the upper limit, it is possible to improve the balance between good dielectric tangent and laser processability.
[0060] (C) Indene resin The indene resin of the present embodiment refers to a (co)polymer containing an indene residue in its skeleton structure and having an average degree of polymerization of 4 to 8, and may be a copolymer of indene (C9H8) with coumarone (1-benzofuran), styrene (C8H8), α-methylstyrene, methylindene, and vinyltoluene. Among these, indene-coumarone copolymer, indene-styrene copolymer, and indene-coumarone-styrene copolymer are preferred.
[0061] That is, the indene resin contains a structural unit A derived from an indene monomer, and may have a structural unit derived from another monomer. Examples of structural units derived from other monomers include a structural unit B derived from a coumarone monomer and a structural unit C derived from a styrene monomer. Specifically, the indene resin may have a structural unit A derived from an indene monomer, a structural unit B derived from a coumarone monomer, and a structural unit C derived from a styrene monomer, or may have a structural unit A derived from an indene monomer and a structural unit B derived from a coumarone monomer, or may have a structural unit A derived from an indene monomer and a structural unit C derived from a styrene monomer. The indene resin may have a repeating structure of these structural units.
[0062] The structural unit A derived from the indene monomer is, for example, one represented by the following general formula (M1).
[0063] [ka]
[0064] (In general formula (M1), R 1 From R 7 are each independently a hydrogen atom or an organic group having 1 to 3 carbon atoms.
[0065] The structural unit B derived from the coumarone monomer is, for example, one represented by the following general formula (M2).
[0066] [ka]
[0067] (In general formula (M2), R C is hydrogen or an organic group having 1 to 3 carbon atoms. C may be the same as or different from each other.)
[0068] The structural unit C derived from the styrene-based monomer is, for example, one represented by the following general formula (M3). [ka]
[0069] (In general formula (M3), R S is hydrogen or an organic group having 1 to 3 carbon atoms. S may be the same as or different from each other.)
[0070] In the above general formulas (M1) to (M3), R1 to R7, RC and RS may contain atoms other than hydrogen and carbon in the structure of the organic group, for example. Specific examples of atoms other than hydrogen and carbon include oxygen atoms, nitrogen atoms, sulfur atoms, phosphorus atoms, silicon atoms, fluorine atoms, chlorine atoms, etc. The atoms other than hydrogen and carbon may include one or more of the above specific examples.
[0071] In the above general formulas (M1) to (M3), R1 to R7, RC and RS are each independently, for example, hydrogen or an organic group having 1 to 3 carbon atoms, preferably hydrogen or an organic group having 1 carbon atom, and more preferably hydrogen.
[0072] In the above general formulas (M1) to (M3), specific examples of the organic groups constituting R1 to R7, RC and RS include alkyl groups such as a methyl group, an ethyl group, and an n-propyl group; alkenyl groups such as an allyl group and a vinyl group; alkynyl groups such as an ethynyl group; alkylidene groups such as a methylidene group and an ethylidene group; cycloalkyl groups such as a cyclopropyl group; and heterocyclic groups such as an epoxy group and an oxetanyl group.
[0073] The indene resin may contain, among others, a copolymer of indene, coumarone and styrene, or a copolymer of indene and styrene, which can improve low dielectric properties.
[0074] Furthermore, the indene resin can have a reactive group in the molecule that reacts with the epoxy group of the epoxy resin, thereby improving the low dielectric properties. Examples of the reactive group include an OH group and a COOH group. The indene resin may have an aromatic structure having a phenolic hydroxyl group inside or at a terminal thereof.
[0075] The upper limit of the weight average molecular weight Mw of the indene resin is, for example, preferably 4000 or less, more preferably 2000 or less, even more preferably 1500 or less, and even more preferably 1200 or less. This improves the compatibility between the indene resin and the epoxy resin, and allows the indene resin to be appropriately dispersed. On the other hand, the lower limit of the weight average molecular weight Mw of the indene resin is, for example, preferably 400 or more, more preferably 500 or more, even more preferably 550 or more, and even more preferably 600 or more. This allows the indene resin to be appropriately dispersed in the resin composition.
[0076] The lower limit of the content of the indene resin is, for example, 1 part by weight or more, preferably 3 parts by weight or more, and more preferably 5 parts by weight or more, based on 100 parts by weight of the resin solid content. This makes it possible to improve the low water absorption property while obtaining a good balance between low dielectric properties and laser processability. On the other hand, the upper limit of the content of the indene resin is, for example, 20 parts by weight or less, preferably 15 parts by weight or less, and more preferably 12 parts by weight or less, based on the entire resin composition of this embodiment. This makes it possible to achieve a balance with other physical properties such as moldability and heat resistance.
[0077] The melting point of the indene resin is preferably 40° C. to 120° C., and the melting point can be controlled by the molecular weight and degree of polymerization.
[0078] The content of component (C) is preferably 0.1 to 20 parts by weight, more preferably 0.5 to 15 parts by weight, and even more preferably 1 to 12 parts by weight, based on 100 parts by weight of the resin solid content.
[0079] By further including the components below, the resin composition of the present embodiment can stably obtain low dielectric properties and good laser processability, and can also improve other physical properties.
[0080] (Polybutadiene elastomer) In this embodiment, the polybutadiene elastomer is a homopolymer or copolymer using a butadiene compound as a monomer component. In this embodiment, from the viewpoint of improving heat resistance, it is more preferable to use a polybutadiene elastomer having a functional group. Examples of the functional group include a vinyl group, an epoxy group, a carboxy group, a hydroxyl group, and a maleic acid group. Among them, from the viewpoint of improving compatibility and adhesion, a polybutadiene having a vinyl group in a side chain is preferable. The copolymer has a segment skeleton formed by polymerization of butadiene in the resin, and examples thereof include styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, acrylate butadiene copolymer, vinylpyridine butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, carboxylated butadiene copolymer, epoxidized butadiene copolymer, etc. Among them, butadiene homopolymer and styrene-butadiene copolymer are preferable from the viewpoint of improving dispersibility and heat resistance.
[0081] The content of the polybutadiene elastomer is preferably 0.1 to 20 parts by weight, more preferably 0.2 to 15 parts by weight, and even more preferably 0.5 to 12 parts by weight, based on 100 parts by weight of the resin solid content.
[0082] (Phenols with unsaturated double bonds) In the present embodiment, phenol having an unsaturated double bond is mainly used from the viewpoint of maintaining a balance between other physical properties while improving dielectric properties and laser processability. Phenol having an unsaturated double bond refers to a compound having a phenol skeleton and having an unsaturated double bond in a substituent of a benzene ring. In this embodiment, examples of phenols having an unsaturated double bond include allylphenol (o-, m- or p-), vinylphenol (o-, m- or p-), allylresorcinol, diallylresorcinol, allylcatechol, diallylcatechol, allylhydroquinone, diallylhydroquinone, allylpyrogallol, triallylphenol, trivinylphenol, triallylresorcinol, trivinylresorcinol, etc. Among them, from the viewpoint of improving adhesion, vinylphenol (particularly p-vinylphenol; 4-ethenylphenol), 2,2'-diallylbisphenol A, o-allylphenol (2-allylphenol), and allylphenol resorcinol type novolak resin are preferred.
[0083] The content of the phenol having an unsaturated double bond is preferably 1 part by weight to 30 parts by weight, more preferably 5 parts by weight to 25 parts by weight, and even more preferably 7 parts by weight to 22 parts by weight, based on 100 parts by weight of the resin solid content.
[0084] (Polyfunctional vinyl compounds) In this embodiment, the polyfunctional vinyl compound refers to a compound having two or more polymerizable unsaturated bonds in the molecule. Examples of the polyfunctional vinyl compounds include bifunctional aromatic vinyl compounds such as divinylbenzene and divinyltoluene; bifunctional (meth)acrylic acid esters such as 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, neopentyl glycol acrylate, allyl acrylate, neopentyl glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate, 3-methylpentanediol diacrylate, and allyl methacrylate; trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, and the like. Examples of the (meth)acrylic acid esters include trifunctional or higher functional (meth)acrylic acid esters such as acrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, pentaerythritol pentaacrylate, pentaerythritol pentamethacrylate, dipentaerythritol hexaacrylate, and dipentaerythritol hexamethacrylate; (meth)acrylic acid esters of polyhydric alcohols such as (poly)ethylene glycol dimethacrylate; diallyl maleate, diallyl fumarate, triallyl cyanurate, triallyl isocyanate, diallyl phthalate, and bis(acryloyloxyethyl) ether of bisphenol A, which may be used alone or in combination of two or more. Among these, (meth)acrylic acid esters of polyhydric alcohols such as (poly)ethylene glycol dimethacrylate; diallyl maleate, diallyl fumarate, triallyl cyanurate, triallyl isocyanate, diallyl phthalate, and bis(acryloyloxyethyl) ether of bisphenol A are preferred, with triallyl isocyanate being more preferred.
[0085] The content of the polyfunctional vinyl compound is preferably 0.5 to 30 parts by weight, more preferably 1 to 20 parts by weight, and even more preferably 4 to 15 parts by weight, based on 100 parts by weight of the resin solid content.
[0086] (Inorganic filler) In this embodiment, examples of inorganic fillers include silicates such as talc, calcined clay, uncalcined clay, mica, and glass; oxides such as titanium oxide, alumina, boehmite, silica, and fused silica; carbonates such as calcium carbonate, magnesium carbonate, and hydrotalcite; hydroxides such as aluminum hydroxide, magnesium hydroxide, and calcium hydroxide; sulfates or sulfites such as barium sulfate, calcium sulfate, and calcium sulfite; borates such as zinc borate, barium metaborate, aluminum borate, calcium borate, and sodium borate; nitrides such as aluminum nitride, boron nitride, silicon nitride, and carbon nitride; and titanates such as strontium titanate and barium titanate. Among these, talc, alumina, glass, silica, mica, aluminum hydroxide, and magnesium hydroxide are preferred, and silica is particularly preferred. As the inorganic filler, one of these may be used alone, or two or more of them may be used in combination.
[0087] The lower limit of the average particle diameter of the inorganic filler is not particularly limited, but may be, for example, 0.01 μm or more, or 0.05 μm or more. This can prevent the viscosity of the thermosetting resin varnish from increasing, and improve the workability when preparing the insulating layer. The upper limit of the average particle diameter of the inorganic filler is not particularly limited, but is, for example, preferably 5.0 μm or less, more preferably 2.0 μm or less, and even more preferably 1.0 μm or less. This can prevent the phenomenon of the inorganic filler settling in the thermosetting resin varnish, and a more uniform resin film can be obtained. In addition, when the circuit dimension L / S of the printed wiring board is less than 20 μm / 20 μm, the influence on the insulation between wirings can be suppressed.
[0088] In this embodiment, the average particle diameter of the inorganic filler can be determined by measuring the particle size distribution of the particles on a volume basis using, for example, a laser diffraction particle size distribution measuring device (LA-500, manufactured by HORIBA Corporation), and taking the median diameter (D50) as the average particle diameter.
[0089] The inorganic filler is not particularly limited, but may be an inorganic filler having a monodisperse average particle size, or an inorganic filler having a polydisperse average particle size. Furthermore, one or more types of inorganic fillers having monodisperse average particle sizes and / or polydisperse average particle sizes may be used in combination.
[0090] The inorganic filler preferably contains silica particles. The silica particles may be spherical. The average particle size of the silica particles is not particularly limited, but may be, for example, 5.0 μm or less, 0.1 μm or more and 4.0 μm or less, or 0.2 μm or more and 2.0 μm or less. This can further improve the filling property of the inorganic filler.
[0091] The lower limit of the content of the inorganic filler is not particularly limited relative to 100 parts by mass of the total solid content of the resin composition, but is preferably 40 parts by mass or more, more preferably 45 parts by mass or more, and even more preferably 50 parts by mass or more. This allows the cured resin film to have particularly low thermal expansion and low water absorption. In addition, warping of the semiconductor package can be suppressed. On the other hand, the upper limit of the content of the inorganic filler is not particularly limited relative to 100 parts by mass of the total solid content of the resin composition, but may be, for example, 85 parts by mass or less, 80 parts by mass or less, or 75 parts by mass or less. This improves handling properties and makes it easier to form the resin film.
[0092] (Flame retardant) In the present embodiment, examples of the flame retardant include halogen-based flame retardants such as bromine-based flame retardants and phosphorus-based flame retardants. Specific examples of the halogen-based flame retardant include bromine-based flame retardants such as pentabromodiphenyl ether, octabromodiphenyl ether, decabromodiphenyl ether, tetrabromobisphenol A, and hexabromocyclododecane, and chlorine-based flame retardants such as chlorinated paraffin. Specific examples of the phosphorus-based flame retardant include phosphate esters such as condensed phosphate esters and cyclic phosphate esters, phosphazene compounds such as cyclic phosphazene compounds, phosphinate-based flame retardants such as phosphinic acid metal salts such as dialkylphosphinic acid aluminum salts, melamine-based flame retardants such as melamine phosphate and polymelamine phosphate. As the flame retardant, each of the exemplified flame retardants may be used alone or in combination of two or more. Among these, phosphorus-based flame retardants are preferred.
[0093] The content of the flame retardant is preferably from 0.1 to 15 parts by weight, more preferably from 0.5 to 10 parts by weight, and even more preferably from 1 to 5 parts by weight, based on 100 parts by weight of the resin solid content.
[0094] (Polymerization initiator) The resin composition of the present embodiment may contain a polymerization initiator. This allows the component (A) to stably cure regardless of the process conditions. The polymerization initiator is not particularly limited as long as it can accelerate the curing reaction between the modified polyphenylene ether and the thermosetting curing agent, and examples thereof include oxidizing agents such as α,α'-bis(t-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, benzoyl peroxide, 3,3',5,5'-tetramethyl-1,4-diphenoquinone, chloranil, 2,4,6-tri-t-butylphenoxyl, t-butylperoxyisopropyl monocarbonate, and azobisisobutyronitrile. These may be used alone or in combination of two or more. In addition, from the viewpoint of further accelerating the curing reaction, a carboxylate metal salt or the like may be used in combination. Among them, α,α'-bis(t-butylperoxy-m-isopropyl)benzene is preferably used. α,α'-bis(t-butylperoxy-m-isopropyl)benzene has a relatively high reaction initiation temperature, and therefore can suppress the promotion of the curing reaction at a time when curing is not required, such as when drying the prepreg, and can suppress the deterioration of the storage stability of the resin composition of this embodiment. Furthermore, α,α'-bis(t-butylperoxy-m-isopropyl)benzene has low volatility, so it does not volatilize during drying or storage of the prepreg, and good stability can be obtained.
[0095] (Coupling Agent) The resin composition of the present embodiment may contain a coupling agent. The coupling agent may be added directly when preparing the resin composition, or may be added to the inorganic filler in advance. The use of the coupling agent can improve the wettability of the interface between the inorganic filler and each resin. Therefore, it is preferable to use a coupling agent, and the heat resistance of the cured resin film can be improved. In addition, the use of the coupling agent can improve the adhesion to the copper foil. Furthermore, since the moisture absorption resistance can be improved, the adhesion to the copper foil can be maintained even in a humid environment.
[0096] The above-mentioned coupling agent may be, for example, a silane coupling agent such as a vinyl-based silane coupling agent, an epoxy silane coupling agent, a cationic silane coupling agent, or an amino silane coupling agent, a titanate-based coupling agent, or a silicone oil-type coupling agent. The coupling agent may be used alone or in combination of two or more kinds. In this embodiment, the coupling agent may contain a silane coupling agent. This makes it possible to increase the wettability at the interface between the inorganic filler and each resin, and further improve the heat resistance of the cured resin film.
[0097] As the silane coupling agent, various types can be used, and examples thereof include epoxy silane, amino silane, alkyl silane, ureido silane, mercapto silane, vinyl silane, and the like.
[0098] Specific examples of the compounds include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, N-phenylγ-aminopropyltriethoxysilane, N-phenylγ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, N-6-(aminohexyl)3-aminopropyltrimethoxysilane, N-(3-(trimethoxysilylpropyl)-1,3-benzenedimethanane, γ-glycidoxypropanol, and the like. Examples of the silane include vinyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, methyltrimethoxysilane, γ-ureidopropyltriethoxysilane, vinyltriethoxysilane, etc., and one or more of these can be used in combination. Among these, vinylsilane, epoxysilane, mercaptosilane, and aminosilane are preferred, and as the aminosilane, primary aminosilane or anilinosilane is more preferred.
[0099] The content of the coupling agent can be appropriately adjusted with respect to the specific surface area of the inorganic filler. The lower limit of the content of such a coupling agent may be, for example, 0.01 parts by weight or more, preferably 0.05 parts by weight or more, relative to 100 parts by weight of the total solid content of the resin composition. When the content of the coupling agent is equal to or more than the lower limit, the inorganic filler can be sufficiently covered, and the heat resistance of the cured resin film can be improved. On the other hand, the upper limit of the content of the coupling agent may be, for example, 3 parts by weight or less, preferably 1.5 parts by weight or less, relative to 100 parts by weight of the total solid content of the resin composition. When the content of the coupling agent is equal to or less than the upper limit, the reaction can be suppressed from being influenced, and the bending strength of the cured resin film can be suppressed from being reduced.
[0100] (Others, additives) The resin composition of the present embodiment may contain additives other than the above-mentioned components, such as resins other than those mentioned above, dyes such as green, red, blue, yellow, and black, pigments such as black pigments, colorants including one or more selected from the group consisting of dyes, stress reducing agents, antifoaming agents, leveling agents, ultraviolet absorbing agents, foaming agents, antioxidants, ion scavengers, rubber components, etc., within the scope of the present invention. These may be used alone or in combination of two or more. Examples of resins other than those mentioned above include thermosetting resins such as epoxy resins and benzocyclobutene resins, thermoplastic resins, phenoxy resins, and cyanate resins.
[0101] (varnish) In this embodiment, the varnish-like resin composition may contain a solvent. Examples of the solvent include organic solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, toluene, ethyl acetate, cyclohexane, heptane, cyclohexane, cyclohexanone, tetrahydrofuran, dimethylformamide, dimethylacetamide, dimethylsulfoxide, ethylene glycol, cellosolve-based solvents, carbitol-based solvents, anisole, and N-methylpyrrolidone. These may be used alone or in combination of two or more kinds.
[0102] When the resin composition is in the form of a varnish, the solid content of the resin composition may be, for example, 30% by mass or more and 80% by mass or less, more preferably 40% by mass or more and 70% by mass or less, which results in a resin composition with excellent workability and film-forming properties.
[0103] The varnish-like resin composition can be prepared by dissolving, mixing, and stirring the above-mentioned components in a solvent using various mixers such as those used in an ultrasonic dispersion system, a high-pressure collision dispersion system, a high-speed rotation dispersion system, a bead mill system, a high-speed shear dispersion system, and a rotation-revolution dispersion system.
[0104] <Manufacturing method of build-up material> The build-up material of the present embodiment is a layer made of a thermosetting resin composition, a prepreg formed by impregnating a fiber base material with a thermosetting resin composition, or a cured product of the prepreg.
[0105] [Layer made of thermosetting resin composition] First, a case where the build-up material of the present embodiment is a layer made of a thermosetting resin composition will be described. The layer made of the thermosetting resin composition can be obtained by forming the above-mentioned resin composition in a varnish state into a film. For example, the layer made of the thermosetting resin composition can be obtained by removing the solvent from the coating film obtained by applying the resin composition in a varnish state. In such a layer made of the thermosetting resin composition, the solvent content can be 5 mass% or less with respect to the entire resin film. In this embodiment, for example, a step of removing the solvent may be performed under conditions of 100°C to 150°C and 1 minute to 5 minutes. This makes it possible to sufficiently remove the solvent while suppressing the progress of curing of the layer made of the thermosetting resin composition containing the thermosetting resin.
[0106] [Prepreg] The prepreg of the present embodiment is formed by impregnating a fiber base material with a thermosetting resin composition. For example, prepreg can be used as a sheet-like material obtained by impregnating a fiber substrate with a resin composition and then semi-curing the same. A sheet-like material having such a structure has excellent properties such as dielectric properties and mechanical and electrical connection reliability under high temperature and humidity, and is suitable for producing insulating layers for printed wiring boards.
[0107] In this embodiment, the method of impregnating the resin composition into the fiber substrate is not particularly limited, but examples thereof include a method of dissolving the resin composition in a solvent to prepare a resin varnish and immersing the fiber substrate in the resin varnish, a method of applying the resin varnish to the fiber substrate using various coaters, a method of spraying the resin varnish onto the fiber substrate using a sprayer, and a method of laminating both sides of the fiber substrate with the resin film consisting of the resin composition.
[0108] Examples of the fiber substrate include glass fiber substrates such as woven glass cloth and nonwoven glass cloth, inorganic fiber substrates such as woven or nonwoven cloth containing inorganic compounds other than glass as components, and organic fiber substrates composed of organic fibers such as aromatic polyamideimide resin, polyamide resin, aromatic polyester resin, polyester resin, polyimide resin, and fluororesin, etc. Among these substrates, the use of a glass fiber substrate typified by glass woven cloth in terms of strength can improve the mechanical strength and heat resistance of the printed wiring board.
[0109] The thickness of the fiber base material is not particularly limited, but is preferably 5 μm to 150 μm, more preferably 10 μm to 100 μm, and even more preferably 12 μm to 90 μm. By using a fiber base material having such a thickness, the handleability during the production of the prepreg can be further improved. When the thickness of the fiber substrate is equal to or less than the upper limit, the impregnation of the resin composition in the fiber substrate is improved, and the occurrence of strand voids and deterioration of insulation reliability can be suppressed. In addition, the formation of through holes by carbon dioxide, UV, excimer, or other lasers can be facilitated. In addition, when the thickness of the fiber substrate is equal to or more than the lower limit, the strength of the fiber substrate and prepreg can be improved. As a result, the handling property can be improved, the preparation of prepreg can be facilitated, and warping of the resin substrate can be suppressed.
[0110] As the above-mentioned glass fiber substrate, for example, a glass fiber substrate formed of one or more types of glass selected from E glass, S glass, D glass, T glass, NE glass, UT glass, L glass, HP glass and quartz glass is suitably used.
[0111] The fiber base material used in this embodiment preferably has a dielectric constant of 3.8 to 7.0 at 1 MHz, more preferably 4.7 to 7.0, and even more preferably 5.4 to 6.8. By using a glass fiber base material having such a dielectric constant, the dielectric constant of the laminate can be further reduced, making it suitable for semiconductor packages using high-speed signals.
[0112] Next, the configuration of printed wiring board 100 of this embodiment will be described in detail.
[0113] The printed wiring board 100 of this embodiment is composed of a substrate 102 and a build-up layer 128 formed on the substrate 102. In this embodiment, the substrate 102 corresponds to a core layer. The build-up layer 128 is comprised of a first circuit layer 104 on the substrate 102 , an insulating layer 106 on the first circuit layer 104 , and a second circuit layer 114 on the insulating layer 106 . Build-up layer 128 may be formed on only one side of substrate 102, or may be formed on each side of substrate 102. In addition, the number of build-up layers 128 stacked on substrate 102 is not particularly limited as long as it is one or more, and may be two or more.
[0114] In this embodiment, the insulating layer 106 is a prepreg formed by impregnating a fiber base material 108 with a thermosetting resin composition.
[0115] The total thickness of the insulating layer 106 is not particularly limited, but is preferably 20 μm or more and 100 μm or less, and more preferably 30 μm or more and 80 μm or less.
[0116] The via hole 116 is a region formed so as to penetrate from the first surface 10 to the second surface 20 of the insulating layer 106. In this embodiment, the via hole 116 has a resin piece 130 extending from the side wall of the via hole 116 to the surface of the first circuit layer 104. In other words, the resin piece 130 covers the first circuit layer 104 exposed at the bottom of the via hole 116 from a portion of the insulating layer 106 exposed in the via hole 116.
[0117] The via hole 116 is configured such that the opening diameter becomes smaller continuously or discontinuously from the first surface 10 to the second surface 20 in a cross-sectional view, and more preferably becomes smaller continuously. The via hole 116 is reduced in diameter from the first surface 10 to the second surface 20. For example, the cross-sectional shape of the via hole 116 may be a tapered shape tapered from the first surface 10 to the second surface 20, or may be a cylindrical shape having a plurality of steps on the side wall. However, the side wall of the insulating layer 106 constituting the via hole 116, which is in the vicinity of the second surface 20, may have a notched region that is notched by soft etching. Here, the soft etching is a different type and process from the method of forming the via hole 116 described later.
[0118] In addition, a part of the fiber base material 108 may protrude into the via hole 116. That is, the fiber base material 108 may have a protruding portion protruding from the side wall of the via hole 116, and the protruding portion may be located inside the conductor 124.
[0119] In a cross section along the thickness direction of the printed wiring board, the protrusions of the fiber base material 108 are spaced apart from each other when they face each other through a conductor 124 (via). In a top view, the protrusions 109 inside the via hole 116 may be configured in a ring shape, or may be configured to be scattered along the outer edge of a circle. In addition, the maximum length of the protrusions 109 in the circumferential direction of the inner wall of the opening may be uniform or non-uniform.
[0120] A conductor 124 is embedded inside the via hole 116. The conductor 124 is a plating layer (metal layer) and is composed of an undercoat film 118 and a plating layer 122. A lower portion of the conductor 124 is provided so as to contact a part of the first circuit layer 104 provided on one surface of the substrate 102. In this embodiment, the conductor 124 serves as an external terminal that electrically connects the first circuit layer 104 and a semiconductor element (not shown).
[0121] The undercoat film 118 is composed of a deposited metal film or an electroless plating film. The undercoat film 118 extends in a film shape along the sidewall of the via hole 116 and the surface of the first circuit layer 104 exposed from the via hole 116, and integrally covers the sidewall of the via hole 116 and the surface of the first circuit layer 104. In this embodiment, the undercoat film 118 is formed on the sidewall of the via hole 116 and on the entire surface of the first circuit layer 104 exposed from the via hole 116. Furthermore, the undercoat film 118 is formed on the sidewall and the upper surface of the second circuit layer 114. The undercoat film 118 may be formed so as to cover the resin piece 103.
[0122] The plating layer 122 is a solid conductor embedded throughout the interior of the via hole 116. In this embodiment, the plating layer 122 is filled inside the base film 118 that covers the inner surface of the via hole 116. That is, the interior of the via hole 116 is composed only of the base film 118 and the plating layer 122. This plating layer 122 may be a single layer or a multilayer. In addition, the plating layer 122 may be formed on the upper surface of the second circuit layer 114 located outside the via hole 116 when the insulating layer 106 is viewed in plan from the first surface 10 side.
[0123] It should be noted that the base film 118 is not essential and may be omitted.
[0124] The first circuit layer 104 is a metal layer such as copper, and has an area electrically connected to the conductor 124 (via). The first circuit layer 104 is disposed on the substrate 102. The first circuit layer 104 is in direct contact with the second surface 20 of the insulating layer 106, and a portion of the first circuit layer 104 covers the opening surface of the via hole 116 from the second surface 20 side, and the conductor 124 (via) is connected to the portion of the first circuit layer 104 exposed from the opening surface.
[0125] <<Printed Wiring Board Manufacturing Method>> Next, a method for manufacturing printed wiring board 100 of this embodiment will be described. 1A to 1C are cross-sectional views showing steps in a manufacturing process for a printed wiring board 100.
[0126] <Core layer formation process> First, a substrate 102 is prepared, with a first metal foil (later a first circuit layer 104) attached to one surface. The substrate 102 is not particularly limited as long as it is made of an insulating material, and can be made of, for example, any of epoxy resin, glass substrate-epoxy resin laminate, glass substrate-polyimide resin laminate, glass substrate-Teflon (registered trademark) resin laminate, glass substrate-bismaleimide-triazine resin laminate, glass substrate-cyanate resin laminate, glass substrate-polyphenylene ether resin laminate, polyester resin, ceramic, resin-impregnated ceramic, etc. The first metal foil may be a metal foil containing at least one of the metal elements such as copper, aluminum, and nickel. Among these, a copper foil having low resistance is preferable. The metal foil may be formed on both sides of the substrate 102 or only on one side.
[0127] The first metal foil is then selectively etched, thereby forming a first circuit layer 104 having a predetermined pattern shape on the substrate 102.
[0128] <Laminate formation process> Next, a laminate in which a second metal foil layer (later the second circuit layer 114) is laminated on at least one surface of an insulating layer 106 made of a prepreg in which a fiber base material 108 is impregnated with a resin composition is laminated on the first circuit layer 104 by applying heat and pressure (see FIG. 1(a)). In FIG. 1(a), the surface on the second metal foil layer side is located on the opposite side to the first circuit layer 104. As the second metal foil layer, for example, it is preferable to use copper foil. The laminate may be a single layer or may have a multi-layer structure. For example, a laminate in which a plurality of prepregs are stacked can be used. As the laminate, a laminate in which an ultra-thin metal foil with a carrier foil is stacked on at least one side and heated and pressurized can be used. The build-up layer may be made of the same material as the core layer (substrate 102), or the fiber base material or resin composition may be different.
[0129] The thickness of the second metal foil layer is preferably 1 μm to 18 μm, more preferably 2 μm to 12 μm. When the thickness of the second metal foil layer is within the above range, a fine pattern can be formed, and warpage can be further reduced by controlling the degree of misalignment.
[0130] Examples of metals constituting the second metal foil layer include at least one of copper and copper-based alloys, aluminum and aluminum-based alloys, silver and silver-based alloys, gold and gold-based alloys, zinc and zinc-based alloys, nickel and nickel-based alloys, tin and tin-based alloys, iron and iron-based alloys, etc. Furthermore, electrolytic copper foil with a carrier may be used as the second metal foil layer.
[0131] <Via formation process> Next, the second metal foil layer (later the second circuit layer 112) is selectively etched using the resist as a mask, thereby forming the second circuit layer 112 having a predetermined pattern (FIG. 1(b)). The second metal foil layer functions, for example, as a circuit pattern extending in a predetermined direction or a rectangular pad in a plan view.
[0132] 1(c), the insulating layer 106 is selectively removed using a laser or the like to form a via hole 116 in the insulating layer 106. The via hole 116 is formed as a through hole penetrating from the first surface 10 to the second surface 20 of the insulating layer 106. The via hole 116 is formed by removing the insulating layer 106 in one direction from the first surface 10 side. In other words, the insulating layer 106 is not removed from the second surface 20 side. A part of the upper surface of the first circuit layer 104 is exposed from the bottom surface (opening surface) of the via hole 116. In this embodiment, a part of the fiber base material 108 may protrude from the side wall of the via hole 116.
[0133] Next, a desmear process is performed on the inside of the via hole 116 of the insulating layer 106. The desmear process is a process for removing smears and the like to clean the surface. The desmear process is not particularly limited, and known methods can be used, such as a wet method using an oxidizing agent solution or the like having an organic matter decomposition effect, and a dry method such as a plasma method in which an object is directly irradiated with active species (plasma, radicals, etc.) having a strong oxidizing effect to remove organic matter residues.
[0134] For example, the desmear process using a chemical solution may specifically include a method in which the resin surface is swelled, then etched by an alkali treatment, and then neutralized. In addition, for example, the desmear process using a plasma treatment is performed by discharging a high-frequency power source of about several kHz to several tens of MHz in a gas atmosphere of several mTorr to several Torr. The gas used may be, for example, a reactive gas such as oxygen, or an inert gas such as nitrogen or argon. The gas components activated by the plasma can remove residues in the via hole and surface dirt due to low molecules by chemical reactions, physical reactions due to collisions (bombering) of the gas molecules themselves, or both, depending on the pressure and the type of gas used. Cleaning by plasma treatment may be performed by, for example, a parallel plate method.
[0135] The desmear process using plasma can remove the residue of the strong resin composition that cannot be completely removed by cleaning with a chemical solution. In addition, the chemical solution does not need to be used. By not using a chemical solution, for example, it is possible to reliably prevent the penetration of the chemical solution into the interface of the wiring layer such as the first circuit layer 104 and the fiber base material 108 and the intrusion of ions. Furthermore, the first surface 10 of the insulating layer 106 can be modified by generating plasma on the exposed surface of the insulating layer 106. This can improve the adhesion between the first surface 10 and the conductor film. In this way, various desmear process methods are appropriately adopted depending on the state of the first surface 10 of the insulating layer 106 or the surface of the inner wall of the via hole 116.
[0136] In this embodiment, there is a resin piece 130 extending from the side wall of the via hole 116 to the surface of the first circuit layer 104. There may be one or more resin pieces 130 in the via hole 116. The shape of the resin piece 130 observed when observing the via hole 116 from above the opening is not particularly limited, and may be circular, approximately circular, or may be a protrusion. In addition, it may have a thickness. However, the resin piece 130 does not cover the entire surface of the first circuit layer 106 exposed at the bottom of the via hole 116, and the area of the resin piece in a plan view is 0.1 to 10% of the total surface area of the first circuit layer 106 exposed at the bottom.
[0137] After the desmear process, an undercoat film 118 is formed on the metal foil layer 114 and on the bottom surface (the first circuit layer 104 exposed from the via hole 116) and sidewall of the via hole 116. The undercoat film 118 may be formed by ion plating, sputtering, vacuum deposition, physical vapor deposition (PVD), or chemical vapor deposition (CVD). The undercoat film 118 may also be formed by electroless plating.
[0138] Next, a plating layer 122 is formed by electroplating inside the opening pattern of the resist layer having a predetermined opening pattern on the undercoat film 118 and on the electroless plating layer. During the plating process, the undercoat film 118 serves as a power supply layer. This undercoat film 118 is formed on the inner wall of the via hole 116. Therefore, the plating layer 122 is embedded inside the via hole 116. As the electroplating, although there is no particular limitation, a known method used in ordinary printed wiring boards can be used, for example, a method of passing a current through a plating solution such as copper sulfate while immersed in the plating solution can be used. The plating layer 122 may be a single layer or may have a multilayer structure. Although there is no particular limitation on the material of the plating layer 122, for example, one or more of copper, copper alloy, 42 alloy, nickel, iron, chromium, tungsten, gold, and solder can be used.
[0139] Next, the resist layer is removed using an alkaline stripping solution, sulfuric acid, or a commercially available resist stripping solution (FIG. 1(d)).
[0140] Next, as shown in FIG. 1(e), the base film 118 and the metal foil layer (later the second circuit layer 114) are removed from the area other than the area where the plating layer 122 is formed (covered with the plating layer 122). For example, the base film 118 and the metal foil layer (later the second circuit layer 114) can be removed by using soft etching (flash etching) or the like. Here, the soft etching process can be performed by etching using an etching solution containing, for example, sulfuric acid and hydrogen peroxide. In this way, the conductor 124 (via) and the conductive circuit can be formed. The conductor 124 (via) is composed of the base film 118 and the plating layer 122. On the other hand, the conductive circuit is composed of the metal foil layer 114 and the metal layer (the base film 118 and the plating layer 122 of the electroless plating layer) laminated together. In this way, the first build-up layer 128 can be formed by forming the conductor 124 (via) in the laminate 110.
[0141] In this manner, printed wiring board 100 of the present embodiment is obtained. Furthermore, printed wiring board 100 obtained in this embodiment may be used as an inner layer circuit board, and a build-up layer may be further formed on this inner layer circuit board.
[0142] <<Semiconductor Devices>> The semiconductor device of this embodiment can be obtained by mounting a semiconductor chip on the printed wiring board 100 of this embodiment. According to the printed wiring board 100 of this embodiment, when the via hole 116 is observed from above the opening, the resin piece 103 is observed, and the resin piece 103 is in contact with the first circuit layer 104 exposed around the bottom of the via hole 116. Such resin piece 103 improves the adhesion between the insulating layer 106 and the first circuit layer 104, thereby improving reliability. In addition, the conductor 124 (via) is embedded in the via hole 116, the opening diameter of which gradually decreases from the first surface 10 to the second surface 20 of the insulating layer 106. Therefore, the adhesion between the insulating layer 106 and the first circuit layer 104 becomes more important.
[0143] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. Below, examples of reference forms are given. 1. A substrate having a first circuit layer on one or both sides; an insulating layer disposed on a surface of the first circuit layer of the substrate; a second circuit layer disposed on a surface of the insulating layer; A printed wiring board comprising: the insulating layer has a via hole penetrating the insulating layer and a conductor embedded in the via hole, and the insulating layer has a dielectric constant Dk (23°C, 10 GHz) of 3.0 to 3.6 and a dielectric loss tangent Df (23°C, 10 GHz) of 0.0001 to 0.006 after curing at 200°C for 90 minutes; a printed wiring board having a resin piece extending from a sidewall of the via hole onto a surface of the first circuit layer; 2. In the printed wiring board according to 1., The printed wiring board, wherein the maximum length l of the resin piece from the side wall of the via hole is 1 to 8 μm. 3. The printed wiring board according to 1. or 2., A printed wiring board, in which, when the thickness of a resin piece at the maximum length l (μm) is d (μm), d / l is 0.065 to 2.5. 4. The printed wiring board according to any one of 1. to 3., The insulating layer has a melt viscosity of 100 to 8,000 Pa·s at 135° C. in the printed wiring board. 5. The printed wiring board according to any one of 1. to 4., The printed wiring board, wherein the insulating layer is a layer made of a thermosetting resin composition, a prepreg formed by impregnating a fiber base material with the thermosetting resin composition, or a cured product of the prepreg. 6. In the printed wiring board according to 5., The fiber base material protrudes into the via hole. 7. The printed wiring board according to 5. or 6., The printed wiring board, wherein the fiber base material comprises one or more fibers selected from the group consisting of a glass fiber base material, a polyamide resin fiber, a polyester resin fiber, a polyimide resin fiber, and a fluororesin fiber. 8. A printed wiring board according to any one of 1. to 7., The thermosetting resin composition constituting the insulating layer of the printed wiring board contains an inorganic filler. 9. The printed wiring board according to 8., The thermosetting resin composition for printed wiring boards contains the inorganic filler in an amount of 5% by mass or more and 60% by mass or less when the total solid content of the thermosetting resin composition is taken as 100% by mass. 10. The printed wiring board according to any one of 1. to 9., The thermosetting resin composition constituting the insulating layer of the printed wiring board comprises one or more selected from the group consisting of modified polyphenylene ether copolymers, maleimide compounds, and indene resins. 11. A semiconductor device comprising a semiconductor element mounted on the circuit layer of a printed wiring board described in any one of 1. to 10. EXAMPLES
[0144] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0145] (Preparation of Resin Composition) Each component was dissolved or dispersed at the solid content shown in Table 1, adjusted with methyl ethyl ketone to a non-volatile content of 70 mass%, and stirred using a high-speed stirrer to prepare a varnish-like resin composition (resin varnish P). The numerical values showing the blending ratio of each component in Table 1 indicate the blending ratio (mass %) of each component relative to the total solid content of the resin composition.
[0146] Details of the raw materials for each component in Table 1 are as follows: (A) Modified polyphenylene ether copolymer: Polyphenylene ether modified with terminal methacrylic groups, "SA9000" manufactured by SABIC Innovative Plastics (B) Maleimide compound: biphenylaralkyl-type maleimide compound, "MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd. (C) Indene resin: indene-coumarone-styrene copolymer containing a phenol group at the end (manufactured by Nitto Chemical Industry Co., Ltd., V-120S, weight average molecular weight: 950, hydroxyl value: 30 mg KOH / g) Polybutadiene elastomer: Polybutadiene, "B-1000" manufactured by Nippon Soda Co., Ltd. Phenol with unsaturated double bonds: Allylphenol, "FATC-809" manufactured by Gun-ei Chemical Co., Ltd. Multifunctional vinyl compound: Triaryl isocyanate, crosslinking agent, "TAIC" manufactured by Mitsubishi Chemical Corporation Inorganic filler: Silica particles, "SC4050", manufactured by Admatechs Co., Ltd. (average particle size 1.1 μm, surface treated with aminophenylsilane) Flame retardant: Condensed phosphate ester "PX-200" manufactured by Daihachi Chemical Industry Co., Ltd. (others) Polymerization initiator: 1,4-bis[(t-butylperoxy)isopropyl]benzene "Perbutyl P" manufactured by NOF Corporation
[0147] (Prepreg) The obtained resin varnish was applied to a woven glass fabric (cloth type #1078, NE glass, basis weight 44 g / m 2 ) was impregnated with the resin using a coating device and then dried for 10 minutes using a hot air dryer at 140° C. to obtain prepreg 1 (build-up material) having a thickness of 70 μm.
[0148] Furthermore, in each of the Examples and Comparative Examples, a resin substrate with a metal foil and a printed wiring board were produced as follows.
[0149] (Preparation of laminated plate with metal foil) Ultra-thin copper foil (Mitsui Mining & Smelting, Microthin FL, 1.5 μm) was laminated on both sides of the obtained prepreg, and the laminate was heated and pressurized at a pressure of 3 MPa and a temperature of 225° C. for 2 hours to obtain a laminate with metal foil. The thickness of the core layer (portion consisting of the resin substrate) of the obtained laminate with metal foil was 0.070 mm.
[0150] (Printed circuit board manufacturing) The obtained laminate with metal foil was used to drill holes at the required locations, and electrical continuity was achieved by electroless plating. The copper foil was then etched to produce a core layer with a circuit formation surface and a copper remaining of 60%. The surface of the core layer facing the copper foil was roughened to a surface roughness of Rz 2.0 μm. Next, prepregs 1 were placed on both sides of the core layer, and an ultra-thin copper foil with a carrier foil (Mitsui Mining & Smelting Co., Ltd., Microthin FL, 1.5 μm) was superimposed thereon, followed by heat-pressure molding for 2 hours at a pressure of 3 MPa and a temperature of 225° C. After that, the carrier foil was peeled off, and the exposed surface of the ultra-thin copper foil was subjected to a roughening treatment to give a surface roughness Rz of 2.0 μm. Next, 400 via holes were formed in the obtained laminate using a carbon dioxide laser. The insides of the vias were immersed in a swelling liquid (Swelling Dip Securigant P, manufactured by Atotech Japan) at 70°C for 10 minutes, and then immersed in an aqueous potassium permanganate solution (Concentrate Compact CP, manufactured by Atotech Japan; sodium permanganate concentration 60 g / l, NaOH concentration 45 g / l) at 80°C for 25 minutes, and then neutralized and roughened. After the process of degreasing, catalyst application, and activation, an electroless copper plating film of about 0.5 μm was formed, a resist was formed, and a pattern of electroplated copper of 20 μm was formed using the electroless copper plating film as a power supply layer, and circuit processing was performed. Next, annealing was performed for 30 minutes at 150 ° C in a hot air drying device, and the power supply layer was removed by flash etching. Next, a solder resist layer was formed, and an opening was formed so that the semiconductor element mounting pad and the like were exposed. Finally, a plating layer consisting of an electroless nickel plating layer of 3 μm and an electroless gold plating layer of 0.1 μm was formed on the circuit layer exposed from the solder resist layer, and the obtained board was cut into a size of 50 mm × 50 mm to obtain a printed wiring board.
[0151] <Verification, measurement and evaluation> The prepreg, the laminate with metal foil, and the printed wiring board were evaluated based on the following evaluation items and in accordance with the criteria shown in Table 2. The results are shown in Table 1. In Table 2, the symbol "~" indicating a range of values indicates a range between the lower limit and the upper limit, or between the lower limit and the upper limit.
[0152] 1) The periphery of the bottom of the above-mentioned via hole was observed with a scanning electron microscope (SEM), and the maximum length l of the resin piece from the wall surface of the bottom of the via hole was measured from the obtained image, and the average value was calculated. In addition, the cross-section of the via hole was observed, the thickness of the resin piece was measured, and the average value d was calculated and the average value was taken. The cross-section observation was performed by cutting the laminate at an arbitrary plane passing through the center of the via hole and observing the cross-section.
[0153] 2) Glass transition temperature The dynamic viscoelasticity measurement was performed in accordance with JISC-6481 (DMA method) using a dynamic viscoelasticity device. The sample used was a laminate with metal foil that had been etched to remove the copper.
[0154] 3, 4) Dielectric constant, dielectric loss tangent The laminate with the metal foil was etched to remove the copper, and measurements were made using a 10 GHz cavity resonator.
[0155] 5) Insulation (reliability) The insulation reliability between vias was evaluated by continuous measurement at 0.1 mm between the vias of the above printed wiring board, under the conditions of an applied voltage of 5.5 V, a temperature of 130°C and a humidity of 85%. The measurement was stopped when the insulation resistance value became less than 106 Ω.
[0156] 6) Via connection reliability The reliability of via connection between layers was evaluated by continuous measurement in a temperature cycle test in which the conductive state was established through the vias of the printed wiring board, and a low temperature treatment of -50°C for 30 minutes was followed by a high temperature treatment of 120°C for 30 minutes was alternately repeated. The test was terminated when the connection resistance value exceeded 15%.
[0157] [Table 1]
[0158] [Table 2] [Explanation of symbols]
[0159] 100 Printed wiring board 102 Substrate 104 First circuit layer 106 Insulating Layer 108 Fiber base material 109 Protrusion 110 Laminate 112 Circuit layer 114 Second Circuit Layer 116 Beer Hall 118 Base film 122 Plating layer 124 Conductor 126 Conductive Circuit 128 Build-up Layer 130 Resin piece
Claims
1. a substrate having a first circuit layer on one or both sides; an insulating layer disposed on a surface of the first circuit layer of the substrate; a second circuit layer disposed on a surface of the insulating layer; A printed wiring board comprising: the thermosetting resin composition constituting the insulating layer contains one or more selected from a polybutadiene-based elastomer, a phenol having an unsaturated double bond, and a polyfunctional vinyl compound; the insulating layer has a via hole penetrating the insulating layer and a conductor embedded in the via hole, and the insulating layer has a dielectric constant Dk (23°C, 10 GHz) of 3.0 to 3.6 and a dielectric loss tangent Df (23°C, 10 GHz) of 0.0001 to 0.006 when cured at 200°C for 90 minutes; a printed wiring board having a resin piece extending from a sidewall of the via hole onto a surface of the first circuit layer;
2. 2. The printed wiring board according to claim 1, The maximum length l of the resin piece from the side wall of the via hole is 1 to 8 μm.
3. 3. The printed wiring board according to claim 1, A printed wiring board, in which, when the thickness of a resin piece at a maximum length l (μm) is d (μm), d / l is 0.065 to 2.
5.
4. 4. The printed wiring board according to claim 1, The insulating layer has a melt viscosity of 100 to 8,000 Pa·s at 135° C.
5. 5. The printed wiring board according to claim 1, The printed wiring board, wherein the insulating layer is a layer made of a thermosetting resin composition, a prepreg formed by impregnating a fiber base material with the thermosetting resin composition, or a cured product of the prepreg.
6. 6. The printed wiring board according to claim 5, The fiber base material protrudes into the via hole.
7. 7. The printed wiring board according to claim 5, The printed wiring board, wherein the fiber base material comprises one or more fibers selected from the group consisting of a glass fiber base material, a polyamide resin fiber, a polyester resin fiber, a polyimide resin fiber, and a fluororesin fiber.
8. The printed wiring board according to claim 1 , The thermosetting resin composition constituting the insulating layer of the printed wiring board contains an inorganic filler.
9. 9. The printed wiring board according to claim 8, The thermosetting resin composition of the printed wiring board contains the inorganic filler in an amount of 5% by mass or more and 60% by mass or less when a total solid content of the thermosetting resin composition is taken as 100% by mass.
10. 10. The printed wiring board according to claim 8, The inorganic filler is treated with aminophenylsilane.
11. The printed wiring board according to any one of claims 1 to 10, A content of the polybutadiene-based elastomer in the printed wiring board is 0.1 parts by weight or more and 20 parts by weight or less per 100 parts by weight of resin solids.
12. The printed wiring board according to claim 1 , A printed wiring board, wherein the content of the phenol having an unsaturated double bond is 1 part by weight or more and 30 parts by weight or less per 100 parts by weight of a resin solid content.
13. 13. The printed wiring board according to claim 1, A printed wiring board, wherein the content of the polyfunctional vinyl compound is 0.5 parts by weight or more and 30 parts by weight or less based on 100 parts by weight of a resin solid content.
14. The printed wiring board according to any one of claims 1 to 13, The thermosetting resin composition constituting the insulating layer of the printed wiring board comprises one or more selected from the group consisting of modified polyphenylene ether copolymers, maleimide compounds, and indene resins.
15. A semiconductor device comprising: a semiconductor element mounted on the circuit layer of the printed wiring board according to claim 1 .
Citation Information
Patent Citations
Metal foil clad laminated sheet and method for drilling non-piercing hole therein
JP2001277426A
Method of manufacturing multilayer printed wiring board
JP2002198659A
Insulating substrate for printed circuit board and printed circuit board
JP2015082661A
Resin composition, resin film, metal-clad laminate, printed wiring board and semiconductor package
JP2019194281A
Resin composition, prepreg, laminated plate, multilayer printed wiring board and semiconductor package
JP2020169273A